Securitization Impacts on Banks Credit Risk: Empirical Evidence from the US Bank Holding Companies - Ruan, Danyue (2012)
The main purpose for this study is to investigate the impact of securitization on banks credit-risk taking behaviour. Previous studies have found that securitization may have either a positive or negative effect on banks insolvency risks. In our paper, we use the U.S. bank holding companies data from 2002 to 2012 covering the period of financial crisis, and select those banks which have done any securitization activities during the period. Using the pooled OLS regression and panel data approach, we observe that securitization is positively related to banks credit risk-taking behaviour. We also find that the positive relationship between credit risk securitization and banks credit risk is predominantly driven by non-mortgage securitized assets, as mortgage securitized assets appear to have no significant impacts on credit risk. Additionally, the results show that banks with more profits are more likely to take risks. Our results indicate that current financial turmoil is associated with credit risk securitization, and once the current problems in credit markets are cleared up, securitization activities may recommence again which in turn may cause another financial turmoil.